1977
DOI: 10.1002/eji.1830071003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of antibody production in plasmacytoma cells by antigen

Abstract: Tissue culture-adapted MOPC 315 mouse plasmacytoma cells which secrete monoclonal anti-DNP IgA antibody, were cultured with a variety of DNP-carrier conjugates and the production of IgA measured by pulse labeling with [3H]leucine and by plaque-forming cell assays. DNP-coupled bovine, human and rabbit gamma-globulins (containing 9 to 12 DNP groups per 50 000 mol wt of carrier) inhibited the synthesis and secretion of IgA by 40 to 80%. This inhibition was specific, since unconjugated globulins were ineffective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

1978
1978
1988
1988

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…It is interesting to note that our results that T-independent IgE antibody-forming cells in atopic patients were specifically in activated with specific antigen are in agree ment with the findings of Okudaira and Ishizaka [5,6] and of other authors [16,17] who showed that multivalent antigens inac tivated antibody forming cells.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It is interesting to note that our results that T-independent IgE antibody-forming cells in atopic patients were specifically in activated with specific antigen are in agree ment with the findings of Okudaira and Ishizaka [5,6] and of other authors [16,17] who showed that multivalent antigens inac tivated antibody forming cells.…”
Section: Discussionsupporting
confidence: 81%
“…Mechanisms related to the receptor blockade [16] may be involved in the antigen-induced suppres sion of IgE antibody production. Consistent results were obtained by Abbas and Klaus [17], who showed that multivalent antigens but not monovalent antigens inhibited anti body production in plasmacytoma cells.…”
Section: Discussionsupporting
confidence: 76%
“…Both B and T cells can serve as targets for the regulatory action ofantiidiotypic antibodies (22)(23)(24). Indeed, idiotype suppression can result from direct interaction of antiidiotypic antibodies with the receptor of the antibody-forming B cell (22) as well as from the induction of idiotype-specific suppressor T cells by antiidiotypic antibody (23).…”
Section: Methodsmentioning
confidence: 99%
“…It has been clearly shown in experimental animals that plasmacytomas, like normal B cells, respond to regulatory signals delivered by antigen, antiidiotypic antibody, and idiotype-specific suppressor T cells (24,25). It has also been shown in inbred as well as outbred animals that autoantiidiotypic antibodies arise during the course ofthe normal immune response and regulate idiotype expression (26)(27)(28).…”
Section: Methodsmentioning
confidence: 99%
“…In these experiments multivalent antigens were observed to inhibit specific antibody secretion by antibody forming cells. More recent in vitro studies suggest that effector cell blockade is not dependent upon Fc receptors and is reversible (42). The precise mechanisms by which multivalent ligands suppress secretion of antibody is unclear, although the elegant study of Hannestad and Gaudernack (43) has suggested that secreted antibody may be arrested in transit through the cell membrane by surface-bound ligands.…”
Section: Discussionmentioning
confidence: 99%